Paradigm shifts for sustainable management of water hyacinth in tropical ecosystems: A review and overview of current challenges - Djihouessi, Metogbe Belfrid; Aina, Martin Pepin; Olokotoum, Mark; Chabi, Louis Claude; Mouftaou, Fohla (My University, 2023)
For decades, the water hyacinth (WH) has progressively proven to be a prevalent invasive plant with significant environmental and socio-economic impacts. Its successful proliferation is enhanced by climate and hydrodynamic conditions (i.e., temperature, water flow regime, nutrient load) which strengthen the intrinsic characteristics of reproduction and germination. Strategies for elimination of the plant such as mechanical removal and application of chemical or biological agents, have been ineffective. Consequently, from the 2000s, management strategies have been reoriented towards the restoration of the structure and functioning of the ecosystem with the pro- gressive integration of various sectors. Henceforth, the much-detailed integrated approach, is struggling to be widely used, and when it is, the effectiveness of the obtained results is mixed. To establish the paradigm shifts necessary for better management of water hyacinth, this review highlights the challenges encountered by control programs tested around the world and underlines the points of attention for the design of a sustainable man- agement strategy. It appears that the absence of primary data collection limits the effective implementation of integrated water hyacinth control programs. Moreover, research innovation, including the development of high- value-added products from water hyacinth, emerges as a key element to obtain sustainable results. Therefore, the choice of a management strategy should be based on a comprehensive economic analysis that integrates the goods and benefits provided by the ecosystem services affected by the presence of water hyacinth. This would make it possible to design fully cost-effective programs that cover monitoring and research costs.
Keywords: Eichhornia crassipes Water hyacinth control Integrated approach Management strategy Valorisation Decision-making